(untitled) (International Journal of Engineering and Computer Science, 2016)
This work presents a novel idea of compression of multi- parameter data encountered in various fields. The advantages of a time domain approach are emphasised. A general mathematical model is proposed that can be adopted for any 3D object. The ease with which the method can be adopted for on line data capture in remote and rural areas is the key aspect of this work.